The Influence of Visual Merchandising, Price Discounts, and Shopping Lifestyle on Impulse Buying Behavior of Generation Z at Miniso Store Galaxy Mall Surabaya - Decinta Putri Ariani; Siti Ning Farida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Business competition in today's globalized era is increasingly tight and dynamic. Local and multinational companies are competing to seize market share, especially in the highly promising retail sector. One of the retail stores in Indonesia that is currently popular among Generation Z is Miniso, which often becomes a destination for Generation Z to browse or purchase unique and cute items. This research aims to determine the influence of visual merchandising, price discounts, and shopping lifestyle on impulse buying among Generation Z at the Miniso store in Galaxy Mall Surabaya. This research uses a quantitative approach. The population of this study is Generation Z, aged 17-27, residing in Surabaya. This study uses a sample of 150 respondents using a non-probability sampling method and a purposive sampling technique. Multiple linear regression analysis was employed to analyze the data, which was processed using SPSS version 27. The results of this study indicate that visual merchandising, price discounts, and shopping lifestyle simultaneously influence impulse buying. Partially, however, visual merchandising does not have a significant effect on impulse buying, while price discounts and shopping lifestyle do have significant effects on impulse buying.